Multimethod Assessment of Design, Metallurgical, and Mechanical Characteristics of Original and Counterfeit ProGlider Instruments - Martins, Jorge N. R. (2022)
Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.